Polypoid Gallbladder Lesion in the Context of Renal Cell Carcinoma - Barbara Seeliger MD; Cosimo Callari MD; Michele Diana MD; Didier Mutter MD, PhD, FACS; Jacques Marescaux MD, FACS, HON FRCS, HON FJSES (SAGE Publishing, 2013)
Introduction . The only curative therapeutic approach for renal cell carcinoma (RCC) is surgery. Laparoscopic surgery for RCC has become an established surgical procedure with equivalent cancer-free survival rate, following the same surgical oncological principles as open surgery. Metastatic RCC of the gallbladder is a rare phenomenon. Hence, there are few reports regarding their management. Case Presentation . We report 2 cases of gallbladder metastasis from clear cell RCC treated by laparoscopic cholecystectomy. The first case was that of a 44-year-old male patient who underwent palliative cholecystectomy, the second case was that of an 83-year-old female patient who is doing well 55 months after surgery without evidence of disease recurrence. Conclusion . The outcome allows us to demonstrate the interest of surgical resection of RCC metastases in the gallbladder by laparoscopic cholecystectomy, respecting surgical oncological principles. Laparoscopic resection of an uncommon gallbladder metastasis can provide long-term favorable outcome.